2002
DOI: 10.1111/j.0014-3820.2002.tb01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Isolating Mechanisms Between Two Sympatric Sibling Species of Sea Snakes

Abstract: Mechanisms that maintain species isolation within sympatric congeners have attracted analysis in many kinds of organisms, but not in snakes. We studied two sibling species of amphibious sea snakes (Laticauda colubrina and L. frontalis) on the island of Efate, in the Pacific Ocean republic of Vanuatu. The two taxa are almost identical morphologically, except that L. colubrina grows much larger than L. frontalis. No natural hybrids have been reported, and geographic distributions of the two taxa suggest the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Differences in chemical signals preclude interspecific mating between related sympatric species (e.g., Cooper andVitt 1986, 1987;Shine et al 2002;Mas and Jallon 2005;Barbosa et al 2006). Different environments may select for different chemical signals in order to, for example, maximize their efficiency (Alberts 1992;Boughman 2002;Symonds and Elgar 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in chemical signals preclude interspecific mating between related sympatric species (e.g., Cooper andVitt 1986, 1987;Shine et al 2002;Mas and Jallon 2005;Barbosa et al 2006). Different environments may select for different chemical signals in order to, for example, maximize their efficiency (Alberts 1992;Boughman 2002;Symonds and Elgar 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual selection is one of the mechanisms that may facilitate speciation due to divergence in male mating signals and female preferences (Boughman 2001;Panhuis et al 2001), and, thereafter, several species recognition mechanisms may prevent interspecific matings (e.g., Shaw & Parsons 2002;Shine et al 2002). Sex pheromones are important for species recognition in many taxa, and like other signals favored by sexual selection, they may play important roles in speciation (Phelan & Baker 1987;McLennan & Ryan 1999;Wyatt 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, two sympatric sea snakes species might be reproductively isolated due to differences in skin scents (Shine et al 2002). Similarly, sexual isolation exists to a degree among populations of red-garter snakes due to variations in female sexual attractiveness pheromones (LeMaster & Mason 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Reptiles use non-behavioral chemical cues of conspecifics to distinguish between the sexes (Brillet, 1993;Cooper and Steele, 1997;Greenberg, 1943;Houck, 2009;Martin and Lopez, 2011;Mason and Gutzke, 1990;Shine et al, 2002). Additionally, studies on E. macularius suggest that sex steroids alter the chemical cues used for sexrecognition (Flores and Crews, 1995;.…”
Section: Testosterone and Non-behavioral Cues Used For Sex Recognitionmentioning
confidence: 99%
“…Studies have also demonstrated that chemical or pheromonal cues play an important role in social interactions of several species of reptiles, including the eublepharid gecko E. macularius, such as for the identification of conspecifics and distinguishing between the sexes (Brillet, 1993;Cooper and Steele, 1997;Greenberg, 1943;Mason and Gutzke, 1990;Shine et al, 2002;reviewed in Houck, 2009;Martin and Lopez, 2011; but see Hews et al, 2011). Furthermore, studies suggest that these chemical cues used for sex recognition may be altered by manipulation of sex steroid levels (Flores and Crews, 1995;.…”
Section: Introductionmentioning
confidence: 99%